Optimal Location of Landfill for Municipal Solid Waste in Qorveh City Using GIS and AHP - amir zareei; vahid kakapour; Jahangir abedi koupai; reza ramezani; sadegh talebi; azadeh nekouei esfahani; sirvan zareei (Mashhad University of Medical Sciences, 2020)
Background and Aim: Waste production is a natural consequence of human life and mismanagement of solid waste can result in environmental hazards. Determination of an appropriate location to sanitary landfill site is one of the most common ways to deal with this crisis. The purpose of this research is to find an appropriate location for landfill site in Qorveh city due to its specific location in terms of agriculture and mining. Materials and methods: The research method in this study was descriptive, analytical and quantitative. In order to locate the landfill, firstly effective information layers in landfill site study (land use layer, rivers, roads, conservation areas, soils, groundwater, morphology, ...) were identified and developed using the collected data from organizations and information centers. Finally,(GIS), (AHP) and (WLC) were used to integrate the maps. Results: The Analytical Hierarchy Process is one of the most efficient techniques designed for multi-criteria decision making, as it enables the formulation of complex problems. Due to limitations, appropriate landfill site options were identified using GIS and used as input data for the hierarchical analysis process. Distance from population centers (towns and villages), distance from surface and groundwater sources are the most important indicators. Conclusion: By combining two methods of multivariate Weighted Linear Combination (WLC) and Analytical Hierarchy Process(AHP) model, the most priority areas were determined with concentration on distance from population centers (towns and villages), distance from surface and groundwater resources,. After extracting the criteria information layers from the maps and prioritizing the 4-storey location ranges, it became clear that the northern direction of Qorveh city with an area of ​​210 hectares is the most suitable area for sanitary landfill of solid wastes.